K+ Channel-SEC11 Binding Exchange Regulates SNARE Assembly for Secretory Traffic. Issue 3 (23rd September 2019) - Waghmare, Sakharam; Lefoulon, Cecile; Zhang, Ben; Liliekyte, Edita; Donald, Naomi; Blatt, Michael R.
Abstract : K + channels initiate a binding exchange with the SNARE SYP121 to trigger SNARE complex assembly and drive secretory vesicle fusion at the plant plasma membrane. Abstract: Cell expansion requires that ion transport and secretory membrane traffic operate in concert. Evidence from Arabidopsis ( Arabidopsis thaliana ) indicates that such coordination is mediated by physical interactions between subsets of so-called SNARE (soluble N-ethylmaleimide-sensitive factor attachment protein receptor) proteins, which drive the final stages of vesicle fusion, and K + channels, which facilitate uptake of the cation to maintain cell turgor pressure as the cell expands. However, the sequence of SNARE binding with the K + channels and its interweaving within the events of SNARE complex assembly for exocytosis remains unclear. We have combined protein-protein interaction and electrophysiological analyses to resolve the binding interactions of the hetero-oligomeric associations. We find that the RYxxWE motif, located within the voltage sensor of the K + channels, is a nexus for multiple SNARE interactions. Of these, K + channel binding and its displacement of the regulatory protein SEC11 is critical to prime the Qa-SNARE SYP121. Our results indicate a stabilizing role for the Qbc-SNARE SNAP33 in the Qa-SNARE transition to SNARE complex assembly with the R-SNARE VAMP721. They also suggest that, on its own, the R-SNARE enters an anomalous binding mode with the channels, possibly as a fail-safe measure to ensure a correct binding sequence. Thus, we suggest that SYP121 binding to the K + channels serves the role of a primary trigger to initiate assembly of the secretory machinery for exocytosis.